Analisis Kelengkapan Pengisian Dokumen Rekam Medis Rawat Inap Pasien BPJS Pada Diagnosis Cephalopelvic Disproportion Di Rumah Sakit Mitra Keluarga Husada Pedan 2019 - Setyawati, Anggi Mega; Zakiyah-Politeknik Kesehatan Bhakti Mulia, Erna (IJMS - Indonesian Journal on Medical Science, 2021)
Abstract : Based on the results of the analysis of 10 medical record documents at the Mitra Keluarga Husada Pedan hospital, there is an incomplete filling of medical record documents.The purpose of this study was to determine the completeness of filling inpatient medical record documents for BPJS patients in the diagnosis og cephalopelvic disproportion at Mitra Keluarga Husada Pedan Hospital in 2019. This type of research is descriptive with a retrospective approach. The population in this study were 173 medical record documents with a sample of 10 medical record documents. Sampling was done by using simple random sampling technique (simple random). The way of collecting data is by observation and interviews. Data processing by colleting, editing, classifying, tabulating and presenting data. The data analysis used was univariate analysis. The results of the research from 10 inpatient medical record documents of BPJS patients on the diagnosis of cephalopelvic disproportion showed that the completeness of the identification review was 10 documents (100%), the completeness of the reporting review was 10 documents (100%), the completeness of the authentication review was 10 documents (100) and completeness in a good recordkeeping review of 8 documents (80%). The results of this study can be concluded that the filling out of medical record documents is not yet complete, it is necessary to conduct a socialization and evaluation regarding filling out medical record documents, as an effort to improve the quality of the completeness of hospital medical record documents.Keywords : identification review, reporting review, authentication review, record review  Abstrak: Berdasarkan hasil analisis  terhadap 10 dokumen rekam medis di Rumah Sakit Mitra Keluarga Pedan masih terdapat pengisian dokumen rekam medis yang belum lengkap. Tujuan penelitian ini adalah untuk mengetahui kelengkapan pengisian dokumen rekam medis rawat inap pasien BPJS pada diagnosis cephalopelvic disproportion di Rumah Sakit Mitra Keluarga Husada Pedan Tahun 2019. Jenis penelitian yang digunakan bersifat deskriptif dengan pendekatan restrospektif. Populasi dalam penelitian ini sebanyak 173 dokumen rekam medis dengan sampel 10 dokumen rekam medis. Pengambilan sampel dilakukan dengan teknik simple random sampling (acak sederhana). Cara pengumpulan data dilakukan dengan observasi dan wawancara. Pengolahan data dengan colleting, editing, klasifikasi, tabulasi dan penyajian data. Analisis data yang digunakan adalah analisis univariat. Hasil penelitian dari 10 dokumen rekam medis rawat inap pasien BPJS pada diagnosis cephalopelvic disproportion diperoleh hasil kelengkapan review identifikasi sebanyak 10 dokumen (100%), kelengkapan pada review pelaporan sebanyak 10 dokumen (100%), kelengkapan pada review autentifikasi sebanyak 10 dokumen (100) dan kelengkapan pada review pencatatan yang baik sebanyak 8 dokumen (80%). Hasil penelitian ini dapat disimpulkan bahwa pengisian dokumen rekam medis sepenuhnya belum lengkap, maka perlu mengadakan sosialisasi dan evaluasi mengenai pengisian dokumen rekam medis, sebagai upaya meningkatkan kualitas dari kelengkapan dokumen rekam medis rumah sakit.Kata Kunci : review identifikasi, review pelaporan, review autentifikasi,  review pencatatan